INNOVATION OF INDONESIAN LEARNING MODELS DURING THE COVID-19 PANDEMIC: A SCIENTIFIC APPROACH WITH MULTIMEDIA (INOVASI MODEL PEMBELAJARAN BAHASA INDONESIA SAAT PANDEMI COVID-19: PENDEKATAN SAINTIFIK DENGAN MULTIMEDIA) - Syahrul Ramadhan; Atmazaki Atmazaki; Vivi Indriyani; Elfia Sukma; Ahmad Johari Sihes (Universitas PGRI Sumatera Barat, 2022)
The COVID-19 pandemic is the biggest problem in education worldwide. In Indonesia, a policy is put in place to implement distance learning called